ETHICAL-LEGAL IMPLICATIONS OF OROFACIAL HARMONIZATION AS A NEW DENTAL SPECIALTY (Interdisciplinary Studies Journal, 2024)
Facial Harmonization has been officially recognized as a new specialty by the Federal Council of Dentistry. This study aimed to examine the ethical and legal implications of dental surgeons performing facial harmonization procedures. A literature review was conducted to analyze regulations, guidelines, and relevant judicial cases related to the practice. Data from professional organizations like the Brazilian Society of Plastic Surgery and the Federal Council of Dentistry were also considered. Despite existing regulations, there has been a rise in media reports of illegal activities and harm caused by practitioners in aesthetic procedures, highlighting the need for stricter oversight. To hold professionals accountable for malpractice, establishing a professional error, proving harm, and establishing a causal link are essential. Unlike typical dental procedures, aesthetic practices are considered obligations of results, shifting the focus to the professional's responsibility for outcomes. The recognition of Facial Harmonization as a new specialty underscores the importance of ethical and legal discussions and calls for a change in the approach of regulatory bodies, educational institutions, and practitioners themselves.
Keywords: Harmonization; Ethics; Legal; Dentistry; Specialty